The development of the uses of ha / ha vái / ha sma vái with or without the narrative perfect and language layers in the old Yajurveda-Saṁhitā texts - Amano, Kyoko (Lingua Posnaniensis, 2019)
It is well known that the perfect with the particle ha is used in the narrative sense in the younger Vedic prose. In the older Vedic prose, Maitrāyaṇī Saṁhitā (MS), Kāṭhaka-Saṁhitā (KS) and Taittirīya-Saṁhitā (TS), there is a certain distribution of past tense categories: the imperfect for the gods myths and the perfect for the past of the period of predecessors. It is supposed that the latter use of the perfect was extended to the area of the former use of the imperfect. In this paper, uses of the particle ha in the three Yajurveda-Saṁhitā texts will be examined. The results suggest that the different uses of ha characterize different language layers in these texts. The following points are of special interest: 1) ha and ha vái with the present verb often characterize a logical consequence derived from the context; hence, they mean “namely, in conclusion”. Many examples of this use are found in MS, but fewer in KS and TS. 2) ha sma (vā́) with the present indicative indicates a repeated and habitual action in the past. In MS, it is almost always used with āha (functionally present) and indicates a ritual opinion of predecessors: “(A predecessor, i.e. Aruṇa Aupaveśi or Keśin Satyakāmi) used to say.” KS and TS have examples with verbs other than āha. 3) ha with the perfect hardly appears in MS, but KS and TS have many examples. 4) ha vai ... uvāca in KS corresponds to ha sma (vā́) āha in MS in the parallel passages. This may be the origin of the narrative use of the perfect. It may be concluded that the language of KS and that of TS are close to each other and that the language of MS has different features from them, even though it is generally supposed that MS and KS belonged to the same branch but TS to another. Moreover, linguistic innovations occurred not always gradually, but through certain innovative authors. This may provide a new perspective for clarifying the relations between the three texts and their process of composition.